2021
DOI: 10.3390/insects12040285
|View full text |Cite
|
Sign up to set email alerts
|

Cuticle Hydrocarbons Show Plastic Variation under Desiccation in Saline Aquatic Beetles

Abstract: In the context of aridification in Mediterranean regions, desiccation resistance and physiological plasticity will be key traits for the persistence of aquatic insects exposed to increasing desiccation stress. Control of cuticular transpiration through changes in the quantity and composition of epicuticular hydrocarbons (CHCs) is one of the main mechanisms of desiccation resistance in insects, but it remains largely unexplored in aquatic ones. We studied acclimation responses to desiccation in adults of two en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(98 reference statements)
0
8
1
Order By: Relevance
“…Populations in more arid areas might have developed enhanced desiccation resistance by local adaptation, but in any case, this would not change our conclusions about the high basal desiccation resistance of the study species. Plasticity in desiccation resistance has been observed at least in one of the species studied here, E. jesusarribasi (Botella-Cruz et al, 2021;. In any case, although intraspecific comparisons could provide important insights about adaptation to desiccation stress, we could assume that variation in desiccation resistance between species is larger than that within species.…”
Section: Non-aridity-relatedmentioning
confidence: 82%
See 1 more Smart Citation
“…Populations in more arid areas might have developed enhanced desiccation resistance by local adaptation, but in any case, this would not change our conclusions about the high basal desiccation resistance of the study species. Plasticity in desiccation resistance has been observed at least in one of the species studied here, E. jesusarribasi (Botella-Cruz et al, 2021;. In any case, although intraspecific comparisons could provide important insights about adaptation to desiccation stress, we could assume that variation in desiccation resistance between species is larger than that within species.…”
Section: Non-aridity-relatedmentioning
confidence: 82%
“…Some aquatic invertebrates possess traits to resist desiccation in situ, but those that lack such traits are forced to disperse (resistance vs. resilience strategies, see Chester & Robson, 2011; Chester et al., 2015 or Strachan et al., 2015 for reviews on this topic). This is the case for water beetles, whose main mechanism to cope with desiccation consists of minimising cuticular transpiration by improving the waterproofing capacity of the cuticle (Botella‐Cruz et al., 2021). Adult beetles disperse among wetted reaches recolonising dry sites when flow returns (Bilton et al., 2001; Cañedo‐Argüelles et al., 2015; Velasco & Millán, 1998), experiencing dehydration during such aerial exposure (Bogan et al, 2017; Strachan et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As predicted, a low RH or high temperature treatment induced a particular plastic physiological response by reducing either CWL or RWL rates. CWL is related to insect epicuticular hydrocarbon composition which change during the adult life stage of some insects to decrease water loss (Benoit & Denlinger, 2010;Botella-Cruz et al, 2021;Chown et al, 2011), and is here shown to be affected by desiccation treatment but not temperature treatment. Lipid phase changes reported at high temperatures in other insects (Gibbs, 2002;Lighton & Feener Jr., 1989;Rourke & Gibbs, 1999) are largely absent in this study, suggesting this is not likely a universal response, or perhaps more sustained thermal variation is required to trigger such a response in our focal species.…”
Section: Excretionmentioning
confidence: 80%
“…Even if basal immune responses in saline species do not trade‐off with other physiological mechanisms, and if saline and freshwater species are exposed to similar infection pressures in nature, the cuticle of saline water beetles might provide a relative advantage in the face of infection challenges compared to their freshwater relatives. The cuticle composition of the saline species studied ( E. jesusarribasi and N. ceresyi ), characterised by a higher proportion of long‐chain hydrocarbons and complex methyl alkanes than their freshwater relatives, may not only result in higher waterproofing and desiccation resistance (Botella‐Cruz et al, 2019, 2021), but also provide a more effective physical and biochemical barrier against the entry of parasites and infectious agents (Marmaras et al, 1996; Noh et al, 2016). In effect, such cuticular changes may represent an exaptation against infection (Gould & Vrba, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Saline water beetles have highly waterproof cuticles, with a lipid component which is more complex and diverse in composition than that of their freshwater congeners, characterised by a high abundance of branched alkanes and few unsaturated alkenes (Botella‐Cruz et al, 2017, 2019). Such properties, along with the plasticity of epicuticular hydrocarbon composition, result in a highly resistant cuticle that has been shown to enhance the ability to cope with osmotic and hydric stress (Botella‐Cruz et al, 2019) and to reduce water loss under desiccation (Botella‐Cruz et al, 2021). The resistant cuticle of saline beetles also may constitute a more effective physical and biochemical barrier against the entry of parasites and pathogens compared to that of freshwater relatives, which could result in a relaxation of other immune defence mechanisms.…”
Section: Introductionmentioning
confidence: 99%